PREDICTORS OF ACADEMIC ACHIEVEMENT FOR FIRST YEAR STUDENTS. THE CASE OF WOLAITA-SODDO UNIVERSITY, ETHIOPIA - Zekarias, Zebdewos; Aba-Milki, Nasser; Mikre, Fisseha (European Scientific Journal, ESJ, 2015)
The objective of this study was to find out the factors that predict first year, first semester academic status of students at Wolaita-Soddo University in 2013/14 academic year. The study involved correlation design that attempted to explore the variables which predict first year university students’ academic achievement. The populations in the study were 3407 first year students enrolled at Wolaita-Soddo University (Ethiopia) in the academic year 2013/14. Of these, 2142(63%) were males and 1265(37%) females and 345 participants were selected by stratified multistage sampling techniques. The data were collected using archival sources and survey questionnaire method. The collected data were analyzed using descriptive statistics and regression analysis. The results of multiple regression analysis showed that grade 12 average mark and university entrance exam score accounted for 43.5% (R2=0. 435, F=129. 2, p<0.05) in achievement and socioeconomic variables explained 18.8% (R2=0.188, F=15.383, p<0.05) of the variance in the first semester university grades respectively. Grade 12 average mark was found to be the variable that relatively accounted for the highest variation in students’ academic achievement. Admission personnel should reconsider to give reasonable weight to grade 12 average marks because of its greater predictive power to university success in the first year study.